Whole-blood and peripheral mononuclear cell transcriptional response to prolonged altitude exposure in well-trained runners - Sutehall, S.; Malinsky, F.; Shurlock, J.; Wang, G.; Bosch, A.; Pitsiladis, Y. P. (Clinical Journal of Sport Medicine, 2023)
Background: Recombinant human erythropoietin (rHuEpo) abuse by athletes threatens the integrity of sport. Due to the overlap in physiological response to rHuEpo and altitude exposure, it remains difficult to differentiate changes in hematological variables caused by rHuEpo or altitude, and therefore, other molecular methods to enhance anti-doping should be explored.